An Analysis of the Effect of Feeder Volume on Shrinkage Porosity Defects in Piston Products through the Gravity Die Casting Process - Nabila Banowati; Veronika Noviaty; Muhammad Fernanda Alvi Yasin; Sugeng Mulyono; Tia Rahmiati; Wandi Wahyudi; Vika Rizkia (MBI, 2024)
To achieve defect-free casting (soundness casting) with a minimal amount of shrinkage porosity, refinement during the casting process is necessary. In the gravity die casting process, there are parameters that lead to product defects, especially in the casting design, focusing on the gating system and feeder system as pathways for the flow of molten metal to supply the molten metal into the mold cavity. This research was conducted to examine the effect of adding feeder dimensions on shrinkage porosity, specifically on Al-Si piston products with a Silicon content of 12-13%. Feeder dimensions were varied in nine variations by adding height and width to the feeder gate, initially measuring 90mm in height and 32mm in width, along with the addition of insulation to the feeder to retain the heat of the casting process. Cooling used water and argon, with water placed at the center core and pin core and argon placed on the outer mold, with a solidification time of 150 seconds and pouring time of 3 seconds considered constant. This study used a Computer Aided Engineering (CAE) approach, namely MagmaSoft or the application of software to model the gravity casting system process. The results showed the lowest percentage of shrinkage at feeder dimensions of 114mm in height and 45mm in width with a mold temperature of 220°C was 0.76% of the product